Intraoperative Evaluation of Whole Sentinel Lymph Nodes Using a One-Step Nucleic Acid Amplification Assay in Endometrial Cancer: A Prospective Study - Shinichi Togami; Nozomi Furuzono; Mika Mizuno; Hiroaki Kobayashi (Medicina, 2025)
Background and Objectives: The aim of this prospective study was to evaluate the diagnostic accuracy of the one-step nucleic acid amplification (OSNA) assay for the intraoperative assessment of sentinel lymph node (SN) metastases, including micrometastases in patients with stage IA low-grade endometrial cancer. Materials and Methods: A prospective analysis was conducted on 204 patients with low-risk endometrial cancer who underwent hysterectomy, bilateral salpingo-oophorectomy, and sentinel node navigation surgery. SNs were analyzed intraoperatively using the OSNA assay, and positive patients underwent systematic pelvic lymphadenectomy. Results: Among the 204 patients included, SN metastases were identified in 12 patients (6%), including 10 patients with micrometastases and 2 patients with macrometastases. No metastases were detected in non-SNs in any of the 12 patients. Recurrence occurred in two patients (1%), involving the vaginal stump and pelvic cavity dissemination, but no lymph node recurrence was observed. The OSNA assay identified a proportion of micrometastases in low-risk endometrial cancer. While a direct comparison with conventional pathological ultra-staging was not performed in this study, the detection rate of micrometastases appears higher than that reported in historical controls. Conclusions: This is the first prospective study to evaluate the intraoperative use of the OSNA assay for whole SNs in endometrial cancer. The results suggest that the OSNA assay enhances the detection of micrometastases, enabling a more accurate assessment of SN metastases. In low-risk endometrial cancer, systematic pelvic lymphadenectomy may be safely omitted in patients with SN-positive micrometastases. Further prospective studies are necessary to validate these findings and support the adoption of this approach in clinical practice.